Bulky Trichomonad Genomes: Encoding a Swiss Army Knife. Issue 10 (October 2016) - Barratt, Joel; Gough, Rory; Stark, Damien; Ellis, John
Abstract : The trichomonads are a remarkably successful lineage of ancient, predominantly parasitic protozoa. Recent molecular analyses have revealed extensive duplication of certain genetic loci in trichomonads. Consequently, their genomes are exceptionally large compared to other parasitic protozoa. Retention of these large gene expansions across different trichomonad families raises the question: do these duplications afford an advantage? Many duplicated genes are linked to the parasitic lifestyle and some are regulated differently to their paralogues, suggesting they have acquired new functions. It is proposed that these large genomes encode a Swiss army knife of sorts, packed with a multitude of tools for use in many different circumstances. This may have bestowed trichomonads with the extraordinary versatility that has undoubtedly contributed to their success. Trends: Trichomonad genomes are exceptionally large, ranging from 86 to 177 Mb. Extensive gene duplication is a major contributor to trichomonad genome complexity. Many trichomonad genes associated with the parasitic lifestyle appear to be specifically duplicated. Phylogenetic analyses suggest that trichomonads have regularly crossed host boundaries throughout their evolution. Some trichomonads still retain this versatility; capable of infecting different host species and switching between disparate parasitic niches.